A small hill to die on : a Penny Brannigan mystery - Duncan, Elizabeth J. (Duncan, Elizabeth J. Penny Brannigan mystery., 2012)
When the pregnant teenage daughter of a wealthy newcomer to Llanelen is found dead in the nearby woods, spa owner Penny Brannigan investigates the family's suspicious financial dealings while her paramour, Detective Inspector Davies, tracks down the killer.